Transdermal delivery of Chinese herbal medicine extract using dissolvable microneedles for hypertrophic scar treatment - Ning, Xiaoyu (2021)
Hypertrophic scars are unfavorable skin diseases characterized by excessive collagen deposition. Although systemic treatments exist in clinic to manage hypertrophic scars, they pose significant side effects and tend to lose efficacy over prolonged applications. Traditional Chinese medicine (TCM) offers as a promising candidate to treat pathological scars. A large number of TCMs have been studied to show anti-scarring effect, however, the natural barrier of the skin impedes their penetration, lowering its therapeutic efficacy. Herein, we reported the use of dissolvable hyaluronic acid (HA) microneedles (MNs) as a vehicle to aid the transdermal delivery of therapeutic agent, a model TCM called shikonin for the treatment of hypertrophic scars. Here, shikonin was mixed with HA to make MNs with adequate mechanical strength for skin penetration, making its dosage controllable during the fabrication process. The therapeutic effect of the shikonin HA MNs was studied in vitro using HSFs and then further verified with quantitative reverse transcriptase polymerase chain reaction. Our data suggest that the shikonin HA MNs significantly reduce the viability and proliferation of the HSFs and downregulate the fibrotic-related genes (i.e., TGFβ1, FAP-α and COL1A1). Furthermore, we observed a localized therapeutic effect of the shikonin HA MNs that is beneficial for site-specific treatment.